Identification and Mercury Sensitivity Test of Rhizosphere Bacteria From Ageratum conyzoides Plants Growing In Ratatotok Gold Mine, North Sulawesi - Rania Nur Farida; Anna Rakhmawati; Tien Aminatun; Sri Atun (Department of Biology Education FMIPA Universitas Negeri Yogyakarta in collaboration with Perhimpunan Biologi Indonesia, 2024)
Indonesia is known for its abundant natural resources, such as gold. However, the mercury-based amalgamation method in illegal gold mining causes environmental pollution. This research explores the potential of utilizing mercury-resistant rhizosphere bacteria from Ageratum conyzoides, a gold hyperaccumulator plant, to develop an effective bioremediation strategy for contaminated gold mining areas. This descriptive-exploratory study aims to identify and determine the sensitivity of mercury in five rhizosphere bacteria isolates from previous research. Bacteria were isolated from the roots of Ageratum conyzoides growing in the Ratatotok gold mining area of North Sulawesi. Bacteria identification was determined using profile-matching methods based on microscopic, macroscopic, physiological, and biochemical features. Similarity Indexes were determined using dendrogram visualization with MVSP software. Mercury sensitivity was analyzed using the cup-plate technique, varying mercury concentrations from 0 ppm to concentrations where clear zones appeared, indicating bacterial growth inhibition. The result indicated that the five isolates were bacteria from the genera Alcaligenes, Pseudomonas, Enterococcus, Streptococcus, and Micrococcus. Notably, Pseudomonas showed the highest potential for mercury resistance, being mercury sensitive at a concentration of 470 ppm, followed by Alcaligenes (110 ppm), Enterococcus (30 ppm), and both Streptococcus and Micrococcus (20 ppm).